2019
DOI: 10.1002/jemt.23342
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness and filler particles characterization of resin‐based composites

Abstract: The purpose of this study was to evaluate the surface roughness (Ra), and the morphology and composition of filler particles of different composites submitted to toothbrushing and water storage. Disc‐shaped specimens (15 mm × 2 mm) were made from five composites: two conventional (Z100™, and Filtek™ Supreme Ultra Universal, 3M), one “quick‐cure” (Estelite ∑ Quick, Tokuyama), one fluoride‐releasing (Beautiful II, Shofu), and one self‐adhering (Vertise Flow, Kerr) composite. Samples were finished/polished using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
70
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 79 publications
4
70
0
5
Order By: Relevance
“…This study demonstrated the color alteration of composite resins induced by different solutions. This data complements the existing studies in the literature 3,8,10,11,30 . Providing subsidies to conclude the different compositions of the resinous matrix can promote different results with natural or synthetic pigmentation drinks.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study demonstrated the color alteration of composite resins induced by different solutions. This data complements the existing studies in the literature 3,8,10,11,30 . Providing subsidies to conclude the different compositions of the resinous matrix can promote different results with natural or synthetic pigmentation drinks.…”
Section: Discussionsupporting
confidence: 89%
“…It was demonstrated that the consumption of beverages able to stain associated with brushing challenges leads to a decrease in microhardness, which was severer in Beautifil II; therefore, the surface treatments reduced the properties of Filtek Z350 XT and Beautifil II. In another study 30 was observed that Beautifil II had the highest values for surface roughness after some superficial treatments. This fact can explain the considerable color alteration in the present study, since the surface roughness can influence the esthetic and biological outcomes of the composites 30 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The same results of this morphological analysis were found in previous studies. 24 As stated by Ruivo et al, 25 the greater the interparticle spacing, the less protected the soft resin matrix against challenges, such as brushing. A point to be borne in mind herein is that roughness values above 0.2 µm allow greater biofilm retention, representing a disadvantage to any material that may be used.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies [16,20] Tanthanuch et al [21] reported an increase in surface roughness and a decrease in microhardness values, for the bulk fill composites stored in food simulating solutions and beverages for 28 days.…”
Section: Discussionmentioning
confidence: 94%